(untitled) (Bangladesh Journal of Botany, 2014)
Effects of crude extract of Microcystis aeruginosa containing microcystin-LR on the germination, growth and chlorophyll content of Zea mays was studied. Soaking of Z. mays seeds for 24 hrs in the cell-free medium during death phase of M. aeruginosa induced a significant reduction in root, shoot lengths, number of lateral roots, fresh and dry weights, leaf area and pigment contents. Soaking of Z. mays seeds for 24 hours in different concentrations of crude extracts of M. aeruginosa (100, 200, 300, 500 and 800 ?g dry cells/ml) from log phase showed inhibitory effect of growth parameters and germination. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18033 Bangladesh J. Bot. 42(2): 295-300, 2013 (December)